TEKNIK PENANGKAPAN DALAM PERIKANAN KEKUAK KOMERSIAL-TRADISIONAL DI BANGKA - YULIAN FAKHRURROZI; JOHN HALUAN; ARI PURBAYANTO; SOEWARNO T. SOEKARTO (Akuatik: Jurnal Sumberdaya Perairan, 2010)
This paper describes the research result on kekuak catching technique applied by Bangka fishermen at two production centres, Pebuar and Nangkabesar. The objectives is exploring and comparing the commercial kekuak catching techniques. Data were collected by observation at fishing activities and interview with key informans. This research found there are three kinds of technique: nyucok, ngerangkang, and nyerampang. Nyucok is the technique came from ancient tradition, but ngerangkang and nyerampang came from fishermen innovation. The nyucok applied at all of regions in Bangka, but the ngerangkang is applied only at Pebuar, and the nyerampang only at Nangkabesar. All of the techniques are not affect to the dry kekuak qualities, and the ngerangkang is the technique that produce the best wet (fresh) kekuak quality.